2015
DOI: 10.1152/japplphysiol.00148.2015
|View full text |Cite
|
Sign up to set email alerts
|

Pneumothorax effects on pulmonary acoustic transmission

Abstract: Pneumothorax (PTX) is an abnormal accumulation of air between the lung and the chest wall. It is a relatively common and potentially life-threatening condition encountered in patients who are critically ill or have experienced trauma. Auscultatory signs of PTX include decreased breath sounds during the physical examination. The objective of this exploratory study was to investigate the changes in sound transmission in the thorax due to PTX in humans. Nineteen human subjects who underwent video-assisted thoraci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…In patients with emphysema [5] and in dogs with pneumothorax [30], a decrease in transmitted amplitude at low frequencies was observed [31], which is qualitatively consistent with the common auscultatory finding of decreased lung sound intensity. In contrast, cardiogenic pulmonary edema was found to increase the amplitude of sound transmitted to the chest wall in dogs in a linear fashion over a wide frequency range relative to postmortem wet-to-dry weight ratios (a measure of the water content of the lungs) [11], a finding consistent with that of bronchial breathing heard over consolidated lung.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In patients with emphysema [5] and in dogs with pneumothorax [30], a decrease in transmitted amplitude at low frequencies was observed [31], which is qualitatively consistent with the common auscultatory finding of decreased lung sound intensity. In contrast, cardiogenic pulmonary edema was found to increase the amplitude of sound transmitted to the chest wall in dogs in a linear fashion over a wide frequency range relative to postmortem wet-to-dry weight ratios (a measure of the water content of the lungs) [11], a finding consistent with that of bronchial breathing heard over consolidated lung.…”
Section: Introductionsupporting
confidence: 61%
“…Sound speeds in the human lung [2, 23, 24, 28, 31, 37] and animal lung [21, 22, 42, 60] have been studied. In human studies, sound was usually introduced into the mouth.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggested the utility of computerized acquisition of these sounds (Mansy et al 2002b;O'Connor et al 2005;Dellinger et al 2008;Pasterkamp et al 1997). Relevant acoustic phenomenon in the pulmonary system have been studied using animal (Kraman and Wang 1990;Mansy et al 2002a;R€ as€ anen et al 2014) benchtop (Acikgoz et al 2008;Dai et al 2015;Mansy et al 2015b) and numerical (Royston et al 1999(Royston et al , 2002Zhang et al 2001;Ozer et al 2007) models. To validate computational models, animal experiments can be carried out (Dai et al 2014a,b;Henry et al 2014;Peng et al 2014Peng et al , 2015.…”
Section: Background Objectivesmentioning
confidence: 99%
“…The E-FAST protocol may assist in assessing the presence of PTX and HTX, and to a lesser extent, its severity. Although the majority of studies present a very high speci city (> 95%) for the diagnosis of PTX in patients with thoracic trauma, they also exhibit a low sensitivity (~ 50%) when compared to other imaging modalities [35]. Prehospital emergency ultrasonography is noninvasive, portable, and inexpensive.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the presence of PTX affected the shape of the sound wave obtained when a 400-1,000 Hz signal was played when compared to a normal lung. Thus, suggesting a potential method for distinguishing between baseline and the presence of PTX [35]. Peng et al presented a computational model simulating acoustic transmission from the lung to the thoracic surface in a porcine model under PTX.…”
Section: Discussionmentioning
confidence: 99%